The effect of finansial rations on the firm value - I Made Suidarma; Kadek Ovy Satyawati; I Putu Denny Dwipayana; I Nyoman Arta Yasa (INOVASI, 2022)
This study aims to determine the effect of profitability, liquidity, and firm size on firm value with firm size as a moderating variable in the consumer sector non-cyclical listed on the IDX for the period 2019-2021. The population of this research is all issuers that are included in the non-cyclical consumer sector, purposive sampling used to select samples so as to produce a total of 31 samples. Using SPSS 26 to process data, the results of this study indicate that profitability has a significant influence with a positive influence on firm value, liquidity and firm size do not have a significant effect. If viewed simultaneously, profitability, liquidity, and firm size have a significant influence on firm value. As a moderating variable, based on research results, capital structure has not been able to strengthen or weaken the relationship between profitability, liquidity, and firm size to firm value.